Pyroelectric response of inhomogeneous ferroelectric-semiconductor films - A.N.Morozovska (Condensed Matter Physics, 2007)
We have modified Landau-Khalatnikov approach and shown that the pyroelectric response of inhomogeneous ferroelectric-semiconductor films can be described by using six coupled equations for the average displacement, its mean-square fluctuation and correlation with charge defects density fluctuations, average pyroelectric coefficient, its fluctuation and correlation with density fluctuations of charged defects. Coupled equations demonstrate the inhomogeneous reversal of pyroelectric response in contrast to the equations of Landau-Khalatnikov type, which describe the homogeneous reversal with sharp pyroelectric coefficient peaks near the thermodynamic coercive field values. Our approach explains pyroelectric loops observed in Pb(Zr,Ti)O3 film.